Inovasi dan Transformasi Pendidikan Islam Melalui SKB 3 Menteri - Arisatul Muwafiqoh; Khoirul Ulum (Universitas Indraprasta PGRI Jakarta, 2023)
Political policy is one aspect that has a significant influence on the development of Islamic educational institutions in Indonesia. Policies always experience changes and dynamics, including in the educational context. Various policies were issued by the government to break down a new idea both in Islamic education and national education. Thus, a new innovation was born called the SKB 3 Ministers. This writing aims to find out how historical, the 3 Ministerial Joint Decree policies, and the innovation and transformation of madrasah education in Indonesia. This study is conducted in 2022 using qualitative research, As for data collection using content analysis, then performed data analysis with a descriptive analysis approach. In this case the author, describes the subject matter in a systematic, comprehensive, and holistic manner. The results obtained from this study are that the 3 Ministerial Decrees are an innovation in the field of Islamic Education in Indonesia. The SKB 3 Ministers does not merely acknowledge the existence of madrasas in the national education system, but rather becomes a form of transformation or change in Islamic education institutions in Indonesia, particularly madrasah institutions. Madrasas, which were originally non-formal educational institutions, have been transformed into formal educational institutions whose position is officially recognized in the National Education System. Then graduates can also continue their education to a higher level of general education.